Immunohistochemical analysis of intestinal biopsies in individuals with celiac disease. Issue 10 (26th August 2022) - Alhabbal, Adel; Abou Khamis, Imad
Abstract: Background and Aims: The immunohistochemical application of CD3 (T lymphocytes) and CD20 (B lymphocytes) markers in duodenal biopsy can facilitate the detection of the number and distribution of intraepithelial lymphocytes along the villi, which is regarded as a key factor for accurate diagnosis of celiac disease. This study aims at finding a relationship between CD3 and CD20 immunohistochemical and histopathological alterations of celiac disease, and at investigating whether the application of those immunohistochemical stainings would improve the detection of lymphocytosis within the epithelium and add advantages to celiac disease diagnosis. Methods: Biopsies were obtained from 100 individuals and stained with hematoxylin and eosin (H&E). They were then evaluated according to the Marsh classification. After that, staining for CD3 and CD20 was individually done and assessed. Results: The overall mean intraepithelial lymphocyte count per 100 enterocytes for H&E was 23.1 (95% confidence interval [CI] = 19.52–26.68), and for immunohistochemistry by CD3 and CD20 was 27.84 (95% CI = 24.31–31.38). The difference was highly significant, P = 0.001. The expression of CD3 immunohistochemically was as follows: Less‐than‐half staining pattern was reported in 16% cases, and half staining pattern was seen in 26%, while most cases 58% had more than half staining pattern. This discovery was consistent with the histological classification of March III among most cases. The expression of CD20 immunohistochemically was as follows: mild crypt involvement was observed in 16% of cases, while moderate crypt involvement and intense crypt involvement were seen in 43% and 41% of cases, respectively. Abstract : The role of immunohistochemical staining for CD3 and CD20 in the diagnosis and evaluation of celiac disease.